Demand for safe spaces - Kondylis, Florence,Legovini, Arianna,Vyborny, Kate,Zwager, Astrid,Andrade, Luiza Cardoso de (World Bank Group, Development Economics, Development Impact Evaluation Group, 2020)
What are the costs to women of harassment on public transit? This study randomizes the price of a women-reserved
10.1596/1813-9450-9269
Keywords: Graue Literatur; sexual harassment; gender; public transit; mobility; revealed preferences; Implicit Association Test; stigma